Overview of Recurrence Mental Health Disorders in Community - Umi Rachmawati; Islamiyah Islamiyah; Firman Firman (Universitas Muhammadiyah Semarang, 2020)
Mental health problems found in the community require comprehensive treatment, as the disease can cause recurrence in the past year after undergoing hospital treatment despite still taking medication. This study aims to find out the picture of recurrence of people with mental disorders in the commut. The design of this research is a type of quantitative research that is descriptive narrative, the population in this study is all people with mental disorders who are in the working area of Poasia Health Center Kendari City and live witha care giver, asmany as 24 people, sampling techniques using purposive sampling techniques obtained as many as 20 respondents. This research was conducted in June 2020 in poasia health center working area of Kendari City, Southeast Sulawesi Province. The data collection tool uses a questionnaire containing the characteristics of respondents and a mental disorder recurrence questionnaire. Data analysis in the form of univariate analysis in the form of frequency distribution. The results showed that almost all respondents experienced a relapse with a high relapse category after undergoing treatment at the hospital.